End‐stage Ankle Arthritis Treated by Ankle Arthrodesis with Screw Fixation Through the Transfibular Approach: A Retrospective Analysis - Haiqiang Suo; Li Fu; Hanguang Liang; Zhiwei Wang; Jie Men; Wei Feng (Orthopaedic Surgery, 2020)
Objective To evaluate the clinical outcome of ankle arthrodesis with screw fixation through the transfibular approach for end‐stage ankle arthritis. Methods Data of 22 patients (28 ankles) with end‐stage ankle arthritis admitted to the Department of Orthopedics and Surgery of the First Hospital of Jilin University from May 2015 to December 2018 were analyzed retrospectively. The study included 9 men and 13 women, with a mean age of 56.86 ± 11.27 years (range, 37–75 years). The mean duration of the disease was 11.36 ± 12.80 years (range, 3 months‐50 years). A total of 16 patients had posttraumatic arthritis, 5 patients had osteoarthritis, and 1 patient had rheumatoid arthritis. There were 12 cases of the left ankle and 16 cases of the right ankle; 16 cases were unilateral and 6 were bilateral. The same surgical procedure was applied to all patients. Collected data included the operation time, intraoperative and postoperative blood loss, hospitalization time, bone union rate, time to bone union, and complications. The American Orthopedic Foot and Ankle Society (AOFAS) ankle hindfoot score and the visual analogue scale (VAS) were used to evaluate the preoperative status and the postoperative outcome at the last follow up. Results The mean follow‐up period was 26.14 ± 10.99 months. The mean operation time was 101.82 ± 33.33 min. The mean blood loss was 116.78 ± 68.86 mL during the procedure and 111.07 ± 52.18 mL after the procedure. The mean hospitalization time was 14.22 ± 5.42 days. Bone union of the ankle joint was achieved in all patients. The mean time to bone union was 14.83 ± 2.14 weeks. There was significant difference in the operation time between the patients undergoing unilateral and bilateral ankle arthrodesis. The AOFAS ankle hindfoot score increased from the preoperative value of 43.46 ± 4.39 points to 80.39 ± 5.37 points at the last follow up. During the same interval, the VAS score improved from 6.14 ± 0.80 points to 1.64 ± 0.73 points. The AOFAS ankle hindfoot score of patients who underwent unilateral ankle arthrodesis improved from the preoperative 43.19 ± 3.95 points to 81.75 ± 5.23 points at the last follow up, and the VAS score improved from 6.19 ± 0.83 points to 1.69 ± 0.70 points. The AOFAS ankle hindfoot score of patients undergoing bilateral ankle arthrodesis improved from the preoperative value of 43.83 ± 5.08 points to 78.67 ± 5.05 points at the last follow up, while the VAS score improved from 6.08 ± 0.82 points to 1.58 ± 0.79 points. There was significant difference in the maximum walking distance and walking on any surface between the patients undergoing unilateral and bilateral ankle arthrodesis. One patient developed superficial peroneal nerve palsy, which resolved within 1 year after the operation. In another patient, healing of the incision skin was delayed. During the follow‐up period, none of the patients developed an infection of the incision or local skin necrosis; screw loosening, withdrawal, or breakage did not occur in any patient. Conclusion The ankle arthrodesis with screw fixation through the transfibular approach provides satisfactory clinical outcomes for end‐stage ankle arthritis.